THE USE OF ‘MARKED CODE’ AS A POPULAR CULTURE TO EXCLUDE UNWANTED PARTICIPANTS - Inkarizki Amalia; Imroatul Mufidah (Universitas Negeri Surabaya, 2023)
Al-Amanah Islamic boarding school has adopted multilingualism so that the obligation to master foreign languages ??is emphasized. The existence of rules for communicating in foreign languages ??encourages students to master Arabic and English. Uniquely, the students still like to share using the languages after graduation. Therefore, this study tries to reveal what foreign languages ??are more often used, what factors make them regulate the choice of language, how is the use of the selected language is pop culture and politeness in choosing the code. This study uses an open questionnaire method so that the data results can be grouped based on several themes. The results of this study indicate that the alumni of Islamic boarding schools prefer to use Arabic rather than English. They also slightly mix up Indonesian and regional languages ??in their conversations. The reason why alumni utilize code-switching is as a marked choice and nostalgia. Meanwhile, they mix foreign languages ??with Indonesian because of unconscious and vocabulary reasons